Ferocious resolve : politics, courage, and what it's like to be a professor - Cyprès, Autumn Tooms, 1965- (Emerald Publishing Limited : Information Age Publishing, Inc., 2015)
This is a critical examination of the people who teach and produce research and scholarship in our institutions of higher education. The insights revealed through probing interviews with individual professors who have made careers in the halls of academia help readers understand the politics, power struggles and perils, both large and small, which shape the modern university. Given the important role these institutions play in our society, such an examination is not only helpful, but essential. This book is a helpful primer for faculty looking to build a career and those interested in understanding how professors are tasked in their profession.